Analisis Perbandingan Performa Framework NestJS dan Lumen Pada Studi Kasus Aplikasi Berbasis REST API - Hanggara, Buce Trias; Nasrullah, Muhammad Hasan; Pramono, Djoko (LPPM STIKI MALANG, 2024)
Information service systems are often developed using web service architectures based on Application Programming Interfaces (APIs). There are various API technologies available, each offering different performance levels. NodeJS and PHP have specific frameworks for backend development, namely NestJS and Lumen. This study focuses on comparing the performance of these applications from the perspective of response time, CPU, and memory usage. The method involves testing 8 services created using each technology. This research provides a comparative analysis showing that there is no significant difference in response time between the two technologies, with only a 40ms or 0.04-second difference. In other aspects, differences were found between the two technologies in terms of CPU usage, with a 6% difference, and memory usage, with a 1% difference. NestJS demonstrated better efficiency in CPU and memory usage compared to Lumen, based on average calculations.